Foodscape Alfresco Dining influencing the image of the urban landscape - Chua, Maureen Alfred G. (College of Architecture, University of the Philippines Diliman, 2011)
The proliferation of alfresco dining has caught the attention of society in contemporary urban setting where eating is not only for daily nourishment but for leisure and recreation as well. People dine outdoors in full view of the public and vice versa., contributing to the character of the streetscape. Streets with ourdoor cafes are now destination areas with identity instead of simply being traffic thoroughfares. Rapid urbanization brings with it a growing population that competes for limited urban spaces. Public spaces, like sidewalks and city squares, are utilized to its maximum capacity unmindful of zoning principles and the imageability of spaces. Today?s alfresco dining spaces, especially those beyond sidewalks and walkways, poses safety and accessibility issues. In addition, the visual quality of the landscape is challenged with the use of elements that either enhance or diminish the landscape character. The study, aimed at determining how alfresco dining facilities help influence urban landscape development, examined commercial areas in Metro Manila where sidewalks and walkways are utilized as an extension of indoor dining areas. Three major types of outdoor dining facilities were identified and classified as: low-end, mid-range and high-end dining. The classification intends to distinguish how alfresco dining spaces help contribute to the image of urban landscapes as demonstrated in areas where they flourish. The study is envisaged to help researchers, concerned regulatory bodies, restaurant owners and operators, the dining public, architects, urban planners and designers, in helping establish alfresco not only as a pleasurable dining experience but as a means to enhance scenic quality in the urban landscape.